X-ray Surgery for Iatrogenic Bile Duct Injury After Laparoscopic Cholecystectomy (Single Center Experience) - O. I. Okhotnikov; M. V. Yakovleva; O. S. Gorbacheva; O. O. Okhotnikov (Неотложная медицинская помощь, 2022)
IM OF STUDY To show the possibilities of antegrade X-ray surgical techniques in the treatment of iatrogenic bile duct injuries after videolaparoscopic cholecystectomy.MATERIAL AND METHODS The study included 24 patients with “minor” and 20 patients with “major” (according to Strasberg) iatrogenic injuries of the extrahepatic biliary tract. Antegrade endobiliary intervention was performed in 26 patients, including the “bridge-procedure” variant preceding the reconstructive surgery. Endobiliary drains were maintained during the reconstructive surgery and in the early postoperative period to control the viability of the anastomosis.When a stricture of the biliodigestive anastomosis (BDA) was detected, balloon dilatation of the anastomotic area was performed. In the subgroup of “minor” injuries, external drainage of the subhepatic biloma in 18 people were supplemented with endoscopic papillotomy in 12 cases.RESULTS In all patients with “minor” injuries of the biliary tree, X-ray surgical techniques were effective. In 11 patients with “major” bile duct injuries, cholangiostomy drainage was gradually transformed into external-internal drainage. In 2 trauma cases of classes D and E temporary antegrade stenting of the duct injury area with a coated self-expanding endobiliary stent was performed. The follow-up period after removal of the antegrade frame drainage ranged from 8 months to 14 years. There were no stricture or failure of BDA.CONCLUSION Short-term external biliary drainage, including the use of rendezvous techniques, may be sufﬁ cient to eliminate the failure of the cystic duct stump. Cholangiostomy drainage, temporary endobiliary stent allow preparing the patient for reconstructive intervention. Drainage marking of the damaged area facilitates the veriﬁ cation of tubular structures in the reconstruction area. Preservation of drainage after reconstructive intervention is the prevention of failure of the biliodigestive anastomosis in the early postoperative period, the development of its stricture in the long term.